2023
DOI: 10.1101/2023.11.07.566145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An acidophilic fungus is integral to prey digestion in a carnivorous plant

Pei-Feng Sun,
Min R. Lu,
Yu-Ching Liu
et al.

Abstract: Carnivorous plant leaves, such as those of the spoon-leaved sundewDrosera spatulata, secrete mucilage which hosts microorganisms potentially aiding in prey digestion. We characterised the mucilage microbial communities and identified the acidophilic fungusAcrodontium crateriformeas the ecologically dominant species. The fungus grows and sporulates on sundew glands as its preferred acidic environment. We show that theA. crateriformehas a reduced genome similar to that of other symbiotic fungi. Based on the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Additionally, fungi inhabiting the mucilage secretions of Drosera enhance prey digestion (Sun et al, 2023), it seems possible that fungi inhabiting these plants endophytically would also be able to contribute to prey digestion via enzyme production. Other fungi are known to inhabit the water contained within carnivorous pitcher plants forming part of a food web that aids in prey digestion, this is seen in Sarracenia purpurea and Nepenthes (Grothjan and Young 2019; Leonora S. Bittleston et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, fungi inhabiting the mucilage secretions of Drosera enhance prey digestion (Sun et al, 2023), it seems possible that fungi inhabiting these plants endophytically would also be able to contribute to prey digestion via enzyme production. Other fungi are known to inhabit the water contained within carnivorous pitcher plants forming part of a food web that aids in prey digestion, this is seen in Sarracenia purpurea and Nepenthes (Grothjan and Young 2019; Leonora S. Bittleston et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the ubiquity of fungal endophytes, it is likely that a range of carnivorous plant -fungal endophyte associations exist. For example, new research has demonstrated that Acrodontium crateriforme, a fungus living in secretions of traps of Drosera spatulata plays a key role in carnivory by aiding in prey digestion: the presence of this fungus reduces digestion time up to 25%, in part by the production of peptidases to aid in breakdown of large proteins (Sun et al, 2023). It is not known, however, whether A. crateriforme exists endophytically inside Drosera, it may only occur inside the external secretions of the plant.…”
Section: Introductionmentioning
confidence: 99%